2017
DOI: 10.3389/fnmol.2017.00176
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Heat Shock Protein B8 (HSPB8) in Motoneuron Diseases

Abstract: Amyotrophic lateral sclerosis (ALS) and spinal and bulbar muscular atrophy (SBMA) are two motoneuron diseases (MNDs) characterized by aberrant protein behavior in affected cells. In familial ALS (fALS) and in SBMA specific gene mutations lead to the production of neurotoxic proteins or peptides prone to misfold, which then accumulate in form of aggregates. Notably, some of these proteins accumulate into aggregates also in sporadic ALS (sALS) even if not mutated. To prevent proteotoxic stresses detrimental to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 113 publications
0
44
0
Order By: Relevance
“…Bag3 also interacts with HspB8 and competes for binding to Hsp70 and Stub1, which increases ALP degradation. The ratio between Bag1 and Bag3 expression levels indicated the preferential degradative pathway that was activated in the cells (43)(44)(45)(46)(47). These data demonstrate that neither HspB8 and Bag3, nor Bag1 mRNA expression were modified after transfection with control IBs and FL TDP-43 IBs compared with vehicle ( Fig.…”
Section: Autophagy and Proteasome Are Not Induced After Fl Tdp-43 Ib mentioning
confidence: 67%
“…Bag3 also interacts with HspB8 and competes for binding to Hsp70 and Stub1, which increases ALP degradation. The ratio between Bag1 and Bag3 expression levels indicated the preferential degradative pathway that was activated in the cells (43)(44)(45)(46)(47). These data demonstrate that neither HspB8 and Bag3, nor Bag1 mRNA expression were modified after transfection with control IBs and FL TDP-43 IBs compared with vehicle ( Fig.…”
Section: Autophagy and Proteasome Are Not Induced After Fl Tdp-43 Ib mentioning
confidence: 67%
“…In mammalian cells, the clearance of aberrantly folded or misfolded proteins is mediated by the intracellular protein quality control (PQC) system 11 . The PQC system is composed of chaperone/co-chaperone proteins, which recognize, bind to and target aberrant proteins to degradation, and the degradative systems, like the ubiquitin proteasome system and the autophagy 12 14 . Chaperones and co-chaperones work in complex; one example is represented by BAG3, a co-chaperone of HSP70 that also binds to the chaperone HSPB8, and the E3 ligase CHIP.…”
Section: Introductionmentioning
confidence: 99%
“…BAG3, a member of six BAG families, contains a conserved domain, and interacts with Hsp-70 [ 6 9 ]. It has been reported that BAG3 is highly expressed in many kinds of primary tumors, including ovarian cancer, and glioblastoma [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%